Initial Reliability and Validity testing of the DESTINY Stroke and Large Vessel Screening Tool - Daniel Nyancho; Ryan Cheung; Aardhra Venkatachalam; Folefac Atem; Sonja Stutzman; Daiwai Olson; Deborah Diercks; Mark Johnson; Roberta Novakovic-White (San Beda University, 2020)
Background: Screening is a valuable tool in emergency medicine for triaging, activation of protocols, and resource allocation. The Dallas Emergency Department Screening Tool to Identify Stroke (DESTINY) was developed to screen for all stroke subtypes, with improved sensitivity for posterior circulation stroke and large vessel occlusion (LVO). The main purpose of this study was to evaluate how reliably the tool could be taught and used by ED Nurses. Methods: This is Phase 1 of a multi-phase study to evaluate the DESTINY tool. A vascular neurologist retrospectively reviewed 409 stroke code activations between January and December of 2018. Thirty descriptive vignettes were composed: right anterior circulation stroke (n=5), left anterior circulation stroke (n=5), posterior circulation stroke (n=5), TIA and stroke mimic (n=6), non-LVO stroke (n=5), and hemorrhagic stroke (n= 4). Fifteen emergency medicine registered nurses used the DESTINY tool to screen the vignettes following the stroke education and DESTINY training module. Results: Individual Pearson Correlation Coefficients (PCC) were calculated for each nurse compared to the vascular neurologist (range: 0.43860 to 0.96966; mean: 0.8746 ± 0.1484). All individual PCC were statistically significant except for one [PCC of 0.43860 (p = 0.0153)]. Cronbach's Alpha scores were very similar across multiple raters (standardized alpha for nurse raters: 0.9853). Omnibus test to compare DESTINY scores by stroke type demonstrated left anterior LVO and mimic/TIA stroke had few outlier observations, however, poorly differentiated hemorrhagic from ischemic stroke Conclusion: As demonstrated by high interrater reliability, the DESTINY tool can be effectively taught to ED nurses using clinical vignettes. The DESTINY tool is good at differentiating non-LVO, anterior LVO, mimics, and TIAs; while the ability to distinguish between anterior LVO/posterior LVO and ischemic/hemorrhagic stroke was sub-optimal. Utilizing the lessons learned in the early version of the DESTINY screening tool we expect that the high-reliability scores will continue to improve in future prospective studies.